Is Penicillin Plus Gentamicin Synergistic Against Sessile Group B Streptococcal Isolates? An in Vivo Study With an Experimental Model of Foreign-Body Infection - Ruppen, Corinne; Mercier, Thomas; Grandgirard, Denis; Leib, Stephen L.; El Haj, Cristina; Murillo, Oscar; Decosterd, Laurent; Sendi, Parham (Frontiers in Microbiology, 2018)
The rate of invasive group B Streptococcus (GBS) infections is steadily increasing, particularly in older persons and in adults with diabetes and other comorbidities. This population includes persons with a foreign body (e.g., who have undergone arthroplasty). In a rat tissue cage model, we evaluated the efficacy of adjunctive gentamicin (GEN) administered systemically (5 mg/kg body weight) every 24 hours, or locally (12.5 mg/L tissue cage concentration) every 24 or 72 hours, in combination with penicillin (PEN) administered systemically (250,000 IU/kg body weight three times per day). The efficacy was evaluated on two different sessile forms of GBS: transition (i.e., in between planktonic and biofilm) and biofilm. After 3 days of treatment, the mean bacterial load reduction of transition-form GBS was greater in all PEN-GEN combination groups than in the PEN monotherapy group (P ≤ 0.03). The 6-day regimen decreased the bacterial load significantly in comparison to the 3-day regimen, irrespective of growth form and adjunctive GEN (P < 0.01). After 6 days of treatment, the mean reduction in transition-form GBS was greater with PEN plus GEN administered locally every 24 hours than with PEN monotherapy (P = 0.03). These results were not confirmed with biofilm GBS. The difference in mean bacterial load reduction between all PEN-GEN and PEN monotherapy groups was <100 CFU/mL. Hence, synergy criteria were not fulfilled. Adjunctive systemic GEN consists of potential side effects and showed poor efficacy in this study. Combining systemic PEN and local GEN has a potential application in the treatment of streptococcal implant-associated infections.